2021
DOI: 10.1609/aiide.v12i2.12887
|View full text |Cite
|
Sign up to set email alerts
|

StarCraft Winner Prediction

Abstract: In game-playing, a challenging topic is to investigate an evaluation function that accurately predicts which player will be the winner of a two-player match. Our work investigates to what extent it is possible to predict the winner of a StarCraft match, regardless of the races that are involved. We developed models for individual match types, and also general models for predicting the winner of non-symmetric matches, symmetric matches, and general matches. The contribution of this paper is (1) a generic and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Related publications focused on in-game player performance analyses and psychological, technical, mechanical or physiological indices. These studies were conducted with use of various video games such as: Overwatch 35,36 , League of Legends [37][38][39][40][41] , Dota 2 [42][43][44][45][46] , StarCraft [47][48][49] , StarCraft II [50][51][52][53][54] , Heroes of the Storm 42 , Rocket League 55 , and Counter-Strike: Global Offensive [56][57][58][59][60] , among others 61 . In some cases a comparison between professional and recreational players was conducted.…”
Section: Related Workmentioning
confidence: 99%
“…Related publications focused on in-game player performance analyses and psychological, technical, mechanical or physiological indices. These studies were conducted with use of various video games such as: Overwatch 35,36 , League of Legends [37][38][39][40][41] , Dota 2 [42][43][44][45][46] , StarCraft [47][48][49] , StarCraft II [50][51][52][53][54] , Heroes of the Storm 42 , Rocket League 55 , and Counter-Strike: Global Offensive [56][57][58][59][60] , among others 61 . In some cases a comparison between professional and recreational players was conducted.…”
Section: Related Workmentioning
confidence: 99%
“…Within the StarCraft community, tasks associated with unit control fall under the umbrella of micro-management, while macro-management encompasses the higher-level game strategy a player pursues. An essential aspect of macro-management is global state evaluation, involving predicting the likelihood of winning based on the current state [8] [14][15] [16]. Build order prediction anticipates the next steps in terms of training, construction, or research given the current state [17] [18].…”
Section: Related Workmentioning
confidence: 99%
“…If the opponent's strategy is predicted, it helps develop AI performance through the use of counter strategy accordingly. Similarly, some studies design mathematical models to predict the winner [14,15]. These studies have shown that they can help predict the outcome of the game.…”
Section: Related Workmentioning
confidence: 99%